PHF-Core Tau as the Potential Initiating Event for Tau Pathology in Alzheimer’s Disease - Luna-Viramontes, Nabil Itzi; Campa-Córdoba, B. Berenice; Ontiveros-Torres, Miguel Ángel; Harrington, Charles R.; Villanueva-Fierro, Ignacio; Guadarrama-Ortíz, Parménides; Garcés-Ramírez, Linda; de la Cruz, Fidel; Hernandes-Alejandro, Mario; Martínez-Robles, Sandra; González-Ballesteros, Erik; Pacheco-Herrero, Mar; et al. (Frontiers in Cellular Neuroscience, 2020)
Worldwide, around 50 million people have dementia. Alzheimer’s disease (AD) is the most common type of dementia and one of the major causes of disability and dependency among older people worldwide. Clinically, AD is characterized by impaired memory accompanied by other deficiencies in the cognitive domain. Neuritic plaques (NPs) and neurofibrillary tangles (NFTs) are histopathological lesions that define the brains with AD. NFTs consist of abundant intracellular paired helical filaments (PHFs) whose main constituent is protein tau. Tau undergoes post-translational changes including hyperphosphorylation and truncation, both of which favor conformational changes in the protein. The sequential pathological processing of tau is illustrated with the following specific markers: pT231, TG-3, AT8, AT100, and Alz50. Two proteolysis sites for tau have been described: truncation at glutamate 391 and at aspartate 421, and which can be demonstrated by reactivity with the antibodies 423 and TauC-3, respectively. In this review, we describe the molecular changes of tau protein as pre-NFTs progress to extracellular NFTs, and during which the formation of a minimal nucleus of the filament, as the PHF-core, occurs. We also analyzed the PHF-core as the initiator of PHFs, and tau phosphorylation as a protective neuronal mechanism against the assembly of the PHF-core.